2012
DOI: 10.1177/0004867412440190
|View full text |Cite
|
Sign up to set email alerts
|

Has electroconvulsive therapy use remained stable over time? A decade of electroconvulsive therapy service provision in Victoria, Australia

Abstract: Objective: Despite the long history of electroconvulsive therapy (ECT) as a psychiatric treatment modality in Australia, existing literature regarding ECT use and practices in Australia is limited. In this unique study, we report ECT provision in Victoria to adults aged 25 years and over from 1998 to 2007, based on complete data from all public and private treatment settings within the State; compare our results to previous literature in the field; and offer possible explanations for these findings as a basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
4
18
0
1
Order By: Relevance
“…Older adults with comorbid depression and medical illness are at risk of further physical compromise through food and fluid refusal and are less likely to tolerate adequate antidepressant pharmacotherapy. 3 Our aforementioned findings concurred with those of earlier population-level studies conducted in Australia. 9 Electroconvulsive therapy has been shown to reduce mortality due to all causes among older depressed individuals 10 and may therefore be a treatment of choice in these clinical situations.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Older adults with comorbid depression and medical illness are at risk of further physical compromise through food and fluid refusal and are less likely to tolerate adequate antidepressant pharmacotherapy. 3 Our aforementioned findings concurred with those of earlier population-level studies conducted in Australia. 9 Electroconvulsive therapy has been shown to reduce mortality due to all causes among older depressed individuals 10 and may therefore be a treatment of choice in these clinical situations.…”
supporting
confidence: 91%
“…The percentage of old-old ECT recipients was less than half the percentage of young-old individuals. 3 In our earlier paper, 3 we reported that most patients were treated for depression, followed by psychosis and other diagnoses in decreasing order. 3 In examining our data further according to age group in the present study, we found women to represent an increasing percentage of patients and men a decreasing percentage of patients with increasing age.…”
Section: Descriptive Statisticsmentioning
confidence: 96%
See 2 more Smart Citations
“…ECT remains the treatment of choice for patients whose physical health is significantly compromised by food and fluid refusal, profound psychomotor retardation, psychotic symptoms or suicidality. Older adults are over-represented among ECT recipients 5,6. Reasons postulated for this finding include a higher incidence of psychomotor retardation and psychotic features among depressed older adults 7…”
Section: Introductionmentioning
confidence: 99%